P163 Effects of Socio–Economic Status on Lung Cancer Stage and Mortality – North-West Perspective. (19th November 2012) - Gudur, S; Patel, V; Sundar, R; Aziz, I; Ashish, A
Abstract : Background: Lung cancer prevalence and mortality has been shown to be higher in the lower socio-economic group in England and Wales. 1 Northwest of England has one of the highest density of economically deprived regions in the country. Our institution caters to a population of approximately 330, 000 in one of the poorest regions of Northwest England. We aimed to analyse the effect of socio–economic status on lung cancer staging on presentation and mortality in our patient cohort. Methods: All patients with newly diagnosed lung cancer patients between 1st Jan–31st Dec 2011 were included in this cross sectional study. Patient data was accessed from our local lung cancer database. Deprivation score as detailed by index of multiple deprivation (IMD) of our cohort were obtained from the local council. Results: Our socioeconomic postcodes showed that there were no patients from the top 10 th centile postcodes of the country in our catchment. However, 37% (93) were in the lowest 20 th centile compared to 20% nationally (2). The disease staging and mortality for top and bottom quartiles is shown in Table 1 . Of 249 patients, 113 (45%) were females. Mean age was 72.4 years (Range 40–97). On diagnosis, 57 (23%) patients had stage 3 and 139 (56%) had stage 4 disease. 162 (65%) of patients died with an average survival after diagnosis of only 62 days (range 31.25– 148.5 days). Conclusions: No significant differences were noted in lung cancer incidence or mortality across socio-economic ends in our local population. Noticeably, there was a high incidence of patients with extensive stage cancer reflecting high mortality. This late presentation may be a reflection of poor health awareness amongst our deprived population belt. A longer study may give us an idea of which areas to target for further education and improvement. References: UK Lung cancer registry, 2011. Cancer incidence and mortality, Office for National Statistics.